Publish or Perish? The Highly Productive Research Elite in European Universities from a Comparative Quantitative Perspective - Kwiek, Marek (My University, 2016)
Research in higher education has consistently shown that some academics publish a lot, while others publish at moderate rates or not at all. Institutional reward and promotion structures have always been focused on research achievements — that is, on publications, and academic prestige comes almost exclusively from research. As shown over the decades by Alfred Lotka, Derek de Solla Price, Robert K. Merton, Jonathan R. and Stephen Cole, Paula Stephan, and Philip G. Altbach, among many others, the majority of university research production comes from a minority of highly productive academics. Literature identifies a number of individual and institutional factors that influence research productivity, including size of the department, disciplinary norms, reward and prestige systems, and individual-level psychological constructs such as a desire for an intrinsic reward of puzzle-solving. Faculty orientation towards research is generally believed to predict higher research productivity; so are: the time spent on research, being a male, faculty collaboration, faculty academic training, years passed since PhD completion, as well as a cooperative climate and support at the institutional level. The “publish or perish” theme refers to both research non-performers (or non-publishers) and top performers. Here we shall focus on high research performance and its correlates from a comparative European perspective.
Keywords: publish or perish; research elite; European higher education; European universities; highly productive academics; research performance; academic productivity; research productivity; inequality in science; research top performers; academic career; academic publishing